ANALISA PEMELIHARAAN BABY INCUBATOR - M. Ariansyah Putra; Harold Situmorang (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2021)
Medical devices are devices that are always in a ready-to-use condition. and can function properly. This requires the Integrated Laboratory of Sari Mutiara University to be able to manage and maintain medical equipment as effectively and efficiently as possible. If this maintenance function is running well, then the quality of the medical equipment used will be good. This research aims to determine the maintenance and care system for the Baby incubator device, know what the Baby incubator is, and to know the principles of work.This research is a descriptive analysis with qualitative methods. The instrument used is by conducting in-depth interviews, observation and documents. The results of this study indicate that in its implementation, the maintenance system cannot be run properly, due to limited technical personnel, lack of training, insufficient maintenance costs, maintenance SOPs are not in accordance with procedures. Planning, organizing, and monitoring are not well implemented so that the preventive and corrective maintenance systems cannot run properly.